2013
DOI: 10.1080/03075079.2011.602667
|View full text |Cite
|
Sign up to set email alerts
|

Why do first-year students of German lose motivation during their first year at university?

Abstract: This article explores motivational changes of first-year students enrolled on German degree courses at two major UK universities. It reports on the qualitative data obtained by a longitudinal mixed-methods study, and focuses on the interplay between students' motivation and the higher education learning environment. In particular, the article aims to shed light on the significant decrease in intrinsic motivation experienced by students over the course of the first year. The qualitative data illustrate the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
4
16
0
1
Order By: Relevance
“…Specifically these data agree with chosen indicators by revealing that feelings of academic competence were particularly important. With this in mind we would support the proposal of Fazey and Fazey (2001), and Busse (2013) that degree students should be given the opportunity to increase their perceived competence in academic tasks at the earliest possible opportunity.…”
Section: Theme One -Can I Do It?mentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically these data agree with chosen indicators by revealing that feelings of academic competence were particularly important. With this in mind we would support the proposal of Fazey and Fazey (2001), and Busse (2013) that degree students should be given the opportunity to increase their perceived competence in academic tasks at the earliest possible opportunity.…”
Section: Theme One -Can I Do It?mentioning
confidence: 99%
“…Indeed, Conceptual Organiser suggests that the most engaged students will be intrinsically motivated. SDT has been well supported by large-scale empirical studies and it has been suggested that it is well suited to explaining the motivation surrounding student engagement (Busse, 2013;Wang & Eccles, 2013;. Moreover, and drawing further on SDT, it suggests students are more likely to be intrinsically motivated if they can develop a sense of belonging within their institution (Russell & Slater, 2011;; if feelings of autonomy can be encouraged (Russell & Slater, 2011;; and if they can develop a sense of competence within their studies (Llorens, Schaufeli, Bakker, & Salanova, 2007;Regaldo, 2003;Russell & Slater, 2011;Yorke & Knight, 2004;Xuereb, 2013;.…”
Section: Factors Influencing Student Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have used the tenets of self‐determination theory to gain a deeper understanding of the relationship among language learning, learner autonomy, and motivation (Benson, ; Ushioda, ). Busse (), in particular, conducted a longitudinal study that explored the motivational changes of first‐year German students who were enrolled in universities in the United Kingdom and found that students’ intrinsic motivation to learn German was connected to the type of classroom tasks, the accompanying student engagement, and the level of challenge associated with these tasks. The study concluded that the appropriate level of intellectual challenge and genuine engagement with learning tasks was the “lynchpin of intrinsic motivation” (Busse, , p. 965) and that language programs should accommodate student choice and agency so as to encourage persistence and uptake in language learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(e.g. Busse 2013;Brahm, Jenert, and Wagner 2017) or performance vs. mastery orientation (e.g. Pintrich 2000).…”
Section: Introductionmentioning
confidence: 99%